WANDA CYPRIANA NORWIDA WOBEC TRADYCJI STAROPOLSKIEJ - Nurzyńska, Agnieszka (Colloquia Litteraria, 2017)
Cyprian Norwid’s Wanda and the Old-Polish Tradition Norwid as a revolutionary and a visionary who reaches towards the roots of Polish literature and himself adds “only a few words” [“tylko parę słów”]? Such a vision of the poet, thinker, and dramatist emerges from the analysis of the mystery play Wanda; this text was once lost and the author edited it for the second time in 1851. The article focuses on three elements of the text that are crucial for its structure: the subtitle, the dedication, and the motto. The analysis of the subtitle “Rzecz w obrazach sześciu” [Object in six images] reveals a discursive composition of the text that is characteristic of Old-Polish dialogues. Reading of the original “Mogile Wandy” dedication while taking into account the contexts of Sęp-Szarzyński and Kochanowski makes apparent Norwid’s reflection on the mythical time and the sacrum time. The interpretation of the motto, which is taken from a seventeenth-century song by Wespazjan Kochowski, emphasizes spatial and at the same time deeply symbolic and political aspects of Norwid’s drama. The mystery play is supposed to furnish spiritual weapons for the people ‘of the North’ to fight the invaders who partitioned Poland. The cursed soil, thanks to the intercession of Wanda who is experiencing her compassio with Christ, will be reintegrated and will become a Blessed soil anew.